Uruguay : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This Information Annex highlights that in August 2011, the Inter-American Development Bank's Board of Executive Directors approved the new Country Strategy with Uruguay (2010-15). Sovereign-guaranteed lending under the new program is expected to reach approximately USD 1.8 billion, which is considered consistent with Uruguay's five-year budget. The program includes additional nonreimbursable financing for technical assistance and analytical work. Lending under the previous Country Strategy (2005-09) reached approximately USD 1.3 billion. It is expected that all four of the Inter-American Development Bank's private sector windows will approve loans and technical assistance in the energy, transport, agribusiness, and global services sectors.